Computer-mediated Diagnostic Assessment of Mixed-ability EFL Learners’ Performance on Tiered Tasks: Differentiating Mediation on Google Meet™ - Fahimeh Rafi; Natasha Pourdana; Farid Ghaemi (Journal of Modern Research in English Language Studies)
Grounded in Vygotsky’s sociocultural theory of mind and the learner-centered approach to second/foreign language acquisition (SLA), this study investigated the extent to which the embedded differentiated instructions and diagnostic assessment, being mediated on Google Meet™ computer-mediated communication platform, would impact the improvement of mixed-ability English-as-a-Foreign-Language (EFL) learners’ English words pronunciation and their degree of engagement in language learning. In a repeated-measures research design, an intact group of 66 EFL learners were partitioned into three tiers of higher, mid- and lower achievers to complete a virtual pretest of listening comprehension, followed by a series of parallel tiered performance tasks of English words pronunciation on a weekly basis. Their task outcomes were subsequently subjected to collective computer-mediated diagnostic assessment. After 10 sessions of intervention, the participants performed on an immediate virtual posttest of listening comprehension, and a post hoc interview. The results of mixed between-within subjects analysis of variance (ANOVA) indicated both the significant learning progress by the tiers, and the outperformance of the lower achievers on the tiered tasks. The statistical results of an analysis of covariance (ANCOVA) similarly reported significant improvement of the tiers’ performance on the pretest-posttest summative assessment in this study. The inductive content analysis of the participants’ responses to the structured interview elicited seven themes which were interpreted as the participants’ strong approval of the usefulness of differentiated instructions, effectiveness of diagnostic assessment, and successful appeal of Google Meet platform.